Design and Evaluation Small Scale Dome Dryer of Corn For Small Industry - I A Longdong, D Tooy (Journal Research of Social Science, Economics, and Management, 2022)
Corn is still an important commodity for small farmer industries in Indonesia. However, one of the problems is the natural drying process with direct sunlight which is quite long and is often disturbed in the rainy season. Reaching 14% moisture content often takes up to 6-7 days so it is not efficient. This is because the direct drying temperature is relatively low, and when it rains it must be moved around, thus increasing labor costs. Several artificial dryers have been developed, but the price is relatively expensive so it is not affordable for small industrial scale. The purpose of this study was to design and evaluate a simple small-scale dome-type dryer. The results showed that the dryers that have been designed and made are quite practical and effective to use for small-scale farmers. Drying time from 35-40% water content to 13.5-14.5% within 2 days with an average drying temperature in the tool 40-56 oC.